(untitled) - Hatch, Walter (Cambridge, 1996)
This book is an incisive analysis of Japan's deepening economic presence in Asia. It challenges neoclassical economists, arguing that instead of simply building a 'yen bloc' or responding to market forces, Japanese business and government elites are working together to build an expanded - and potentially exclusive - production zone. The authors suggest that the transplantation of many standard Japanese business practices in Asia is based on the concept of keiretsu (enterprise group) which allows a complex web of production networks to develop. The book shows that such strategic control of technology is a unique model of globalisation. While informed by economic theory, Asia in Japan's Embrace is highly accessible, containing interviews and anecdotal evidence from factory floors and board rooms. It is comprehensive and controversial, outlining policy implications and the impact on global trade...